1989
DOI: 10.1002/cne.902800205
|View full text |Cite
|
Sign up to set email alerts
|

Forms and measures of adult and developing human corpus callosum: Is there sexual dimorphism?

Abstract: The sexual dimorphism of the human corpus callosum (CC) is currently controversial, possibly because of difficulties in morphometric analysis. We have reinvestigated the issue by using morphometric techniques specially designed to yield objective measurements of CC size and shape. The development of the CC was studied with similar techniques in order to investigate whether its final shape and size might be influenced by axonal elimination, as could be expected from previous animal studies. We have measured the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
181
1
3

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(197 citation statements)
references
References 35 publications
10
181
1
3
Order By: Relevance
“…Finally, the studies exploring regional differences in CC size are particularly difficult to interpret since methods of CC partitioning vary across studies (reviewed in Bishop and Wahlstein 96 ), including in S research, and the size of the CC partitions can be influenced by CC shape. 70 On the whole, the majority of the studies found a reduction of the CC in the schizophrenics, as also noticed in a review 97 of 27 imaging studies published between 1986 and 2000. At first glance, these conclusions seem to support the hypoconnectivity hypothesis.…”
Section: Morphological Studiesmentioning
confidence: 70%
See 3 more Smart Citations
“…Finally, the studies exploring regional differences in CC size are particularly difficult to interpret since methods of CC partitioning vary across studies (reviewed in Bishop and Wahlstein 96 ), including in S research, and the size of the CC partitions can be influenced by CC shape. 70 On the whole, the majority of the studies found a reduction of the CC in the schizophrenics, as also noticed in a review 97 of 27 imaging studies published between 1986 and 2000. At first glance, these conclusions seem to support the hypoconnectivity hypothesis.…”
Section: Morphological Studiesmentioning
confidence: 70%
“…The main factors determining callosal size in development appear to be the increase in-axon diameter and myelination. 28,70 Even a considerable loss of callosal axons could be masked by an increase in the diameter of the remaining ones, which is what one would expect if the remaining axons, as suggested above, sprout into vacated territories. The same cautions must be applied to the interpretation of regional differences in CC size.…”
Section: Developmental-pathogenic Scenariosmentioning
confidence: 81%
See 2 more Smart Citations
“…Cowell et al (28) and (29) were also excluded because they use the same raw data as Allen et al (4). Clarke et al (25) and Prokop et al (102) were each treated as two separate studies because two different methods were used to examine two different groups of subjects in each study. Holloway et al (66) was treated as three separate studies because three different samples of subjects were examined.…”
Section: Selection Of Studiesmentioning
confidence: 99%